2023
DOI: 10.1186/s13578-023-00992-x
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl itaconate is effective in host-directed antimicrobial responses against mycobacterial infections through multifaceted innate immune pathways

Abstract: Background Itaconate, a crucial immunometabolite, plays a critical role in linking immune and metabolic functions to influence host defense and inflammation. Due to its polar structure, the esterified cell-permeable derivatives of itaconate are being developed to provide therapeutic opportunities in infectious and inflammatory diseases. Yet, it remains largely uncharacterized whether itaconate derivatives have potentials in promoting host-directed therapeutics (HDT) against mycobacterial infect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Kim et al report host-directed therapeutic effects against mycobacterial infections. In their study, itaconate significantly suppressed the production of interleukin-6 and 10, whereas it enhanced phagosome maturation [151].…”
Section: Metabolomics Of Biofilm As Diagnostic and Therapeutic Targetmentioning
confidence: 86%
“…Kim et al report host-directed therapeutic effects against mycobacterial infections. In their study, itaconate significantly suppressed the production of interleukin-6 and 10, whereas it enhanced phagosome maturation [151].…”
Section: Metabolomics Of Biofilm As Diagnostic and Therapeutic Targetmentioning
confidence: 86%
“…If a sufficient amount of itaconate is located in the airway and/or readily available to the macrophages encountering mycobacteria it could potentially serve to completely halt and/or eliminate any bacterial proliferation. A recent study by Kim et al found that dimethyl itaconate (DMI) could be a promising candidate for host-directed therapeutics against both MTB and NTM due to its ability to activate multiple innate immune responses [84].…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, ITA reduces intracellular Escherichia coli at later time points in macrophages, at least in part by increasing phagocytosis and bactericidal activity ( 41 ). In addition, DMI suppresses intracellular growth of Mtb, M. avium , even of multidrug resistant Mtb in macrophages, partly associated with the induction of autophagy ( 22 ). In Zika virus infection of neurons, receptor interacting protein kinase 1 (RIPK1) and RIPK3 signaling suppresses viral replication via IRG1-mediated ITA production ( 42 ).…”
Section: Roles Of Ita In Infectionmentioning
confidence: 99%